Reproductive biology and utilisation of Berchemia discolor (Klotzsch) Hemsley (Rhamnaceae) - Lusepani, Nakwezi Esther (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.